Assessing emerging technologies from an arms control perspective - Brackmann, Maximilian; Gemünden, Michèle; Invernizzi, Cédric; Mogl, Stefan (Frontiers in research metrics and analytics, 2022)
Developments in science and technology improve health and wellbeing of humankind, for example with better methods to detect and treat diseases. However, some advances have led to the development of weapons of mass destruction: chemical and biological weapons. Although banned by international treaties, chemical weapons have been used in recent years in assassinations and the Syrian civil war. Additionally, biological weapons became the subject of recent suspicions and allegations. While not limited to these fields, the so-called dual-use potential—the possibility to apply aspects both with benevolent or malevolent intentions—is especially pronounced in the life sciences. Here, we showcase some areas explored at the conference series Spiez CONVERGENCE that facilitates an exchange between science, arms control and international security. Together, these communities discuss the potential impact of life scientific advances on the Chemical and Biological Weapons Conventions. Enabled by digital technologies, DNA sequencing and synthesis provide the toolbox to (re)construct viruses and cells, which demonstrated invaluable during the COVID-19 pandemic but bear the misuse risk to allow intentionally triggering an outbreak. Open databases and algorithms could be used to generate new chemical weapons. We argue that preventing unintended consequences of life science research while promoting its benefits with responsible science, requires awareness and reflection about unexpected risks of everyone involved in the research process. The strength of the ban of chemical and biological weapons also depends on scientists interacting with policy makers in evaluating risks and implementing measures to reduce them.